Εργαλεία και μηχανισμοί χρηματοδότησης της νεοφυούς επιχειρηματικότητας στην Ελλάδα - Μόρντο, Βασίλειος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων (ΙΙ). Εργαστήριο Βιομηχανικής και Ενεργειακής Οικονομίας, 2018)
The ultimate goal of this thesis is to study and research the Greek funding environment for startup companies and the opportunities that exist for them. This is the first attempt ever to fully map the aforementioned environment. The introduction focuses on the rationale of a thesis on startup funding and presents the concept of entrepreneurship and its distinct forms. A brief explanation of startup entrepreneurship and its way of functioning as well as an analysis of startup contribution to the economy follows, in order to highlight its financial impact. The strategy followed on a national and European level in order to boost startup entrepreneurship is also mentioned. In the third chapter of the thesis, Greece’s funding environment is reviewed, with the help of a number of relevant studies. Then follows a theoretical review of the role of the different constituents of such an environment and more specifically of the role of: (a) friends and family, (b) national and European funding tools, (c) venture capital funds, (d) angel investors, (e) bank financing, (f) microfinance, (g) peer-to-peer lending platforms, (h) crowdfunding, (i) startup competitions and (j) startup supporting structures. The next part presents the methodology used in the field study, including interviews with stakeholders from the Greek startup ecosystem. The field study emphasized on the advantages, problems and opportunities in the startups’ funding environment in Greece. The interviews were conducted with the aim to get different perspectives from professionals of diverse backgrounds and interest groups, in order to form an as accurate view of the domestic funding environment as possible. Sixteen interviews were conducted in total, with an average duration of approximately one hour and 2 additional professionals were contacted for the purpose of knowledge transfer with seasoned members of the Greek startup ecosystem. Topics covered were focused on 4 key areas: 1. Understanding the progress of funding opportunities in Greece over time. 2. Realizing the effectiveness of the different sources of funding in the country. 3. Estimating the future impact of the investments made through the Equifund Fund-of-Funds program. 4. Listing the existing problems, opportunities and proposals in regards to improving the operating conditions of the ecosystem in the future. The thesis concludes with an attempt to draw conclusions as a result of matching the findings of the field study and the theoretical research. Using these conclusions and the stakeholders’ recorded opinions as the key reference points, a list of proposals that could potentially lead to the amelioration of the current funding opportunities for startup companies, thus fueling further growth for the Greek startup ecosystem, is presented.